Pulmonary Atresia with Intact Ventricular Septum and Absence of Tricuspid Valve. A Report of Four Cases - Adel E. González Morejón; Ansia Serrano Sánchez; Giselle Serrano Ricardo (Medisur)
Pulmonary atresia with intact ventricular septum suggests a simple congenital heart malformation. However, nothing could be further from the truth. Among the morphological peculiarities of this condition, the presence of congenitally unguarded tricuspid valve orifice is rarely observed. The present paper aims at describing a series of four patients with both malformations detected in the William Soler Children’s Heart Center from 1986 through 2012. Echocardiographic diagnosis could be accurately performed in the last two patients; identification of the initial cases was established by the findings at necropsy. All patients underwent Blalock – Taussig shunt as initial palliative treatment, which was associated with balloon atrioseptostomy in two cases. Only one of the last children mentioned survived. Vital prognosis of patients suffering from this association of malformations lies in early echocardiographic detection.